2016
DOI: 10.1128/jvi.00809-16
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Rabies Virus Phosphoprotein Isoforms in Pathogenesis

Abstract: Rabies virus (RABV) P gene mRNA encodes five in-frame start codons, resulting in expression of full-length P protein (P1) and N-terminally truncated P proteins (tPs), designated P2, P3, P4, and P5. Despite the fact that some tPs are known as interferon (IFN) antagonists, the importance of tPs in the pathogenesis of RABV is still unclear. In this study, to examine whether tPs contribute to pathogenesis, we exploited a reverse genetics approach to generate CE(NiP)⌬P2-5, a mutant of pathogenic CE(NiP) in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…A recent study conducted with spring viremia of carp virus (another vesiculovirus) showed the ability of the P protein to regulate the immune cellular response by decreasing IFN production ( Li et al, 2016 ). This is consistent with the evolutionary role of this protein to antagonize IFN activities in other Rhabdoviruses such as rabies virus ( Rieder and Conzelmann, 2011 ; Okada et al, 2016 ) and makes the P protein an interesting target for future studies of VSV virulence.…”
Section: Discussionsupporting
confidence: 76%
“…A recent study conducted with spring viremia of carp virus (another vesiculovirus) showed the ability of the P protein to regulate the immune cellular response by decreasing IFN production ( Li et al, 2016 ). This is consistent with the evolutionary role of this protein to antagonize IFN activities in other Rhabdoviruses such as rabies virus ( Rieder and Conzelmann, 2011 ; Okada et al, 2016 ) and makes the P protein an interesting target for future studies of VSV virulence.…”
Section: Discussionsupporting
confidence: 76%
“…Plasmids expressing Nluc-encoding minigenome of RABV-CVS (pCAGGS-RVDInluc) were generated following the construction strategy of firefly luciferase expressing pCAGGS-RVDI-luc (Okada et al, 2016). As a result, RABV-CVS minigenome contains 5' trailer region of RABV-CVS strain, an ORF of Nluc gene, the 3' leader region of RABV-CVS strain instead.…”
Section: Plasmid Construction and Rabv Minigenome Assaymentioning
confidence: 99%
“…P also guides nascently folded RNA-free N (N 0 ) to newly synthesized genomic RNA during replication [19]. Up to five alternative start codons result in five N-terminally truncated P protein variants, which have been implicated as Type-1 IFN antagonists [21]. This is accomplished through direct interaction with STAT1 and STAT2 proteins as well as suppressing IRF-3 [22][23][24].…”
Section: Introductionmentioning
confidence: 99%